Implementation science evaluation of an eHealth pediatric primary-care overweight and obesity intervention using the RE-AIM evaluation framework - Joshua S. Yudkin; Rebecca M. Jungbauer; Marlyn A. Allicock; Sarah E. Barlow (PLoS ONE, 2026)
Introduction The childhood overweight and obesity (OW/OB) epidemic in the United States disproportionately affects children from marginalized backgrounds, particularly those who lack the financial resources or support to engage in evidence-based interventions. Moreover, healthcare systems struggle to deliver these interventions equitably. To address this gap, this study evaluated the implementation science outcomes of Dynamo Kids! (DK!), a novel primary-care-based eHealth intervention intended for families with children ages 6–12 with OW/OB. Materials and methods DK! was developed within a major safety-net hospital system in Dallas, TX. Ten providers in three different clinics were instructed to offer DK! to 581 families with children ages 6–12 with OW/OB. Guided by the Reach, Effectiveness, Adoption, Implementation Maintenance (RE-AIM) framework, we evaluated the implementation science outcomes of the DK! pilot conducted between August 2020 and April 2021, using eight different data sources—both qualitative and quantitative. Results Building on previously published findings that demonstrated an increase in Family Nutrition Physical Activity score and a decrease in child%BMIp95, this study engaged 46 families and ten providers with diverse backgrounds in a safety-net practice who, generally, self-reported improved knowledge, skills, and self-efficacy in treating overweight and obesity. Most parents were satisfied with the DK! intervention, using the website with high variability, on average for two hours 24 minutes of total user time over three months and endorsed the patient-centered care in qualitative interviews. Both families and providers generally found DK! to be important, trustworthy, tailored, and accessible and endorsed the DK! intervention. Discussion DK! demonstrated limited success in its initial setting, with strong support for its continuation and expansion from both the healthcare system and patient families. Future studies should incorporate user recommendations and consider comparing outcomes to a control group beyond the context of the COVID-19 pandemic.